EFFICACY AND SAFETY OF BAN HUANG ORAL LIQUID FOR TREATING BOVINE RESPIRATORY DISEASES - Li, Bing; Zhou, Xu-Zheng; Niu, Jian-Rong; Wei, Xiao-Juan; Li, Jian-Yong; Yang, Ya-Jun; Liu, Xi-Wang; Cheng, Fu-Sheng; Zhang, Ji-Yu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Ban Huang oral liquid was developed as a veterinary compound preparation by the Lanzhou Institute of Husbandry and Pharmaceutical Sciences of the Chinese Academy of Agricultural Sciences (CAAS). The purpose of this study was to determine whether the oral liquid preparation of traditional Chinese medicine, Ban Huang, is safe and effective for treating respiratory diseases in cattle. Materials and Methods: Acute oral toxicity experiments were conducted in Wistar rats and Kunming mice via oral administration. The minimum inhibitory concentration of the drug against Mycoplasma bovis in vitro with the double dilution method was 500 mg/mL, indicating good sensitivity. The results of laboratory pathogen testing, analysis of clinical symptoms, and analysis of pathological anatomy were combined to diagnose bovine respiratory diseases in 147 Simmental cattle caused by mixed infections of M. bovis, bovine respiratory syncytial virus, bovine parainfluenza virus type 3, and Mannheimia haemolytica. These cattle were randomly divided into three groups: drug treatment group 1 (treated via Tilmicosin injection), drug treatment group 2 (treated with Shuang Huang Lian oral liquid combined with Tilmicosin injection), and drug treatment group 3 (treated with Ban Huang oral liquid combined with Tilmicosin injection). Treatment effects were observed within 7 days. Results: The results showed no toxicity and a maximum tolerated dose greater than 20 g/kg BW. For the 87 cattle in drug-treatment group, the cure rate was 90.80%, whereas the response rate was 94.25%. The cure rate of drug treatment group was increased by 14.13% in comparison with that of drug control group 1 and by 7.47% in comparison with that of drug control group 2 (both P < 0.05). Conclusion: This study demonstrates that Ban Huang oral liquid is a safe and effective treatment for bovine respiratory diseases, especially for mixed infection caused by M. bovis, bacteria, and viruses.